Foreign Students’ Study in the “Flagship Universities” of the Russian Federation within the Context of “Soft Power” Implementation - I. V. Arzhanova; D. V. Dydzinskaya; E. A. Musina; P. S. Seleznev (Высшее образование в России, 2019)
The article discusses the mechanisms, models, best practices of the organization foreign students’ study in the cohort of “flagship universities” of the Russian Federation according to the policy of “soft power”. The purpose of this article is to determine the possibility and feasibility of using international cooperation of flagship universities as a tool of “soft power” implementation. The universities extend their partnership activities with the long-term goals to promote a positive image of our country, to ensure their development as well as the development of RF regions of their localization. The article is aimed at the elaboration of recommendations addressed to universities and education authorities. The statistical basis for the analysis was the monitoring data on the effectiveness of Russian universities (published data for 2017 and preliminary data for 2018). Factual information is based on the results of the development programs of flagship universities for 2017–2018. It should be noted that such an analysis is carried out for the first time and it is the first step towards the consideration of the international activities of flagship universities within the concept of “soft power”.